(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The urinary tract includes the kidneys, ureters, bladder and urethra. In the evolution of vertebrates, including humans, has been differentiated three types of kidneys, each of which is an improvement over the previous. This review focuses on some topics concerning the embryological development of the kidney and urinary tract, as well as molecules associated with its development and finally the phylogeny of the kidney in vertebrates.